STUDENTS’ ACCEPTANCE TOWARDS THE USE OF GOOGLE CLASSROOM IN LEARNING ENGLISH - Nabela Fadlilah Nabela; Ayu Istiana Sari (English Education Department Slamet Riyadi University Surakarta, 2022)
This research aimed to find out the students’ acceptance towards the use of Google Classroom in learning English at the Seventh Grade Students of SMPN 27 Surakarta 2022 / 2023 Academic Year. This study was conducted at the seventh grade students of SMPN 27 Surakarta in the Academic Year 2022/2023. This study applied Descriptive Qualitative (QD). The research was conducted on June-July in 2022/2023 Academic Year. The subject of the research was 32 students of VII A at SMPN 27 Surakarta. In collecting the data, the researcher used questionnaire to students in a form of Google Form and interview with English teacher. To analyze the data, the researcher used qualitative method. The result of this research showed that the used of Google Classroom as an e-learning media has advantages and disadvantages. Google Classroom could help the students learning English easier and make the learning process more interesting. It also showed that with the use of Google Classroom could enhance students’ English skills and more creative. However, there were some obstacles that faced by the students during the use of Google Classroom, that the problem of internet network and quota limited. Keywords : Students’ Acceptance, Google Classroom, A Descriptive Study